The Relationship between Statistical Thinking Skills and Students' Ability to Solve Problems on Mean, Median, and Mode - Ivatun Mardiyah; Della Indrian Maharani; Asper Van Dijk (Relevancia: Jurnal Pendidikan dan Pembelajaran, 2024)
One of the important factors that affect the quality of Natural Resources (HR) is education. Since the early stages of formal education, mathematics lessons have become an integral part in the development of logical thinking and data analysis skills. Mathematics is a very important subject, but in practice it is often considered difficult and less popular by some students. One branch of mathematics taught in schools is statistics. The reality in the field shows that statistical material, especially on the topic of mean, median, and mode, is still not fully mastered by most students. This can be caused by the lack of students' statistical thinking skills, which are the ability to understand, analyze. This study aims to analyze the strength and direction of the relationship between statistical thinking skills and students' ability to solve problems on basic statistical material, especially the material on mean, median, mode. This study was conducted on students in class VIII of Muhammad Shodiq Middle School. The approach used in this study uses a correlational method, which aims to identify and measure the relationship between two variables without providing a direct causal interpretation. The data collection technique was carried out through a written test, which was designed to measure the two research variables, namely statistical thinking skills and the ability to solve basic statistical material questions. The population in this study was 150 students, and 50 students were selected as samples. The results showed that out of 50 students, 13 students (32.5%) were at level 1 of the introduction stage, 22 students (55%) were at level 2 of the analysis stage, and 5 students (12.5%) were at level 3 of the sequencing stage. Although students' abilities in calculating mean, median, and mode were generally good, the results of the analysis showed that none of the students reached a higher level of statistical thinking. Based on the results of the data analysis, it can be concluded that there is a positive and significant relationship between statistical thinking skills and students' abilities in working on questions on basic statistics material. It turns out that students who have higher statistical thinking skills are usually also more adept at solving questions about mean, median, and mode. The higher the level of thinking, the better the results.